Under- or overexpansion of education? Trends in qualification mismatch in the United Kingdom and Germany, 1984-2017 - Jonas Wiedner (Social Science Research, 2024)
Prominent theoretical positions in sociology and labor economics disagree whether educational expansion has outstripped the demand for qualified labor (overexpansion), or whether economies face a skill shortage despite increases in education (underexpansion). Focusing on the United Kingdom and West Germany, two countries with dissimilar skill formation institutions, patterns of expansion, and labor markets, this paper asks to what degree expansion of education has been absorbed. I point out shortcomings of wage-centered analyses and develop an approach that focuses on trends in self-assessed over- and underqualification. Using repeated surveys among workers and official labor market statistics, I estimate regression models that link the cohort-level expansion of education to the cohort-level prevalence of mismatch. Results suggest overexpansion in the United Kingdom, with overqualification increasing and underqualification decreasing over historical times and cohorts. West Germany, on the other hand, shows signs of underexpansion. While dominant theoretical accounts focus on the under-/overexpansion of tertiary education, my results show that mismatch-dynamics in both contexts are strongest for workers without university degrees.
Keywords: 320; Educational expansion; Mismatch; Occupational change; Comparative research